Optix drives the repeated convergent evolution of butterfly wing pattern mimicry (2011)
Mimicry—whereby warning signals in different species evolve to look similar—has long served as a paradigm of convergent evolution. Little is known, however, about the genes that underlie the evolution of mimetic phenotypes or to what extent the same or different genes drive such convergence. Here, we characterize one of the major genes responsible for mimetic wing pattern evolution in Heliconius butterflies. Mapping, gene expression, and population genetic work all identify a single gene, optix, that controls extreme red wing pattern variation across multiple species of Heliconius. Our results show that the cis-regulatory evolution of a single transcription factor can repeatedly drive the convergent evolution of complex color patterns in distantly related species, thus blurring the distinction between convergence and homology.